Faktor yang Dipertimbangkan Buyer dalam Keputusan Pembelian Hasil Laut Olahan Produksi Indonesia - Ferrinadewi, Erna; Rukismono, Martinus (UNUSA Press, 2018)
Abstract: Considering Indonesia’s marine goods has big potential and world’s fish consumption per capita which is 20kgs per year, we should be able to utilize it maximally. It will become biggest contribution to Indonesia’ economy as maritime country. However, in reality Indonesia marine goods export tends to decrease 3.25% since 2014 and marine export contribution to PDB so far is no more than 30%. UKM face problem in expanding market area and competition in international marine goods processed where Thailand and Vietnam has more competitive price. This objective of this research is identifying what consideration factors of international buyer in their decision to buy Indonesia marine goods. It involves 10 buyers of Gulama bubbles, Snapper bubbles, Manyung bubbles and Kurau bubbles. Data gathered through depth interview with respondent personally and later on describes and analyses deeper. The result of analysis is researcher able to identify a number of consideration factors used by buyer in their decision to buy fish bubbles and sea cucumber which are colour, freshness, fish type, moistures, hygiene factors and sales service speed.